Adenoid Hypertrophy Managed With Artemisia Cina Dilution: A Study of Two Cases (Bioresearch Communications, 2023)
Adenoid hypertrophy, is the enlargement of adenoid tissues in the nasopharynx, a common concern among children and often exhibits with nasal congestion, mouth breathing, snoring, and sleep disturbances. Spontaneous healing of enlarged adenoid is common in adolescents and adults, however, in this case study, we present two instances of pediatric patients who demonstrated adenoid-related health issues. After a thorough evaluation, and based on the principle of symptom similarity Artemisia cina was prescribed; this treatment continued for three consecutive weeks, and a follow-up lateral x-ray of nasopharynx was obtained one more week later. The use of homeopathic preparation of Artemisia cina appeared to ease their symptoms. This outcome suggests that Artemisia cina may hold promise as a homeopathic option for managing adenoid-related concerns in pediatric patients. However, we acknowledge that further research and a larger sample size are necessary to establish the usefulness of this approach.Bioresearch Commu. 10(1): 1449-1452, 2024 (January)